Sei Alsengemmen a Brescia - Elisabetta Gagetti (Pallas, 2010)
Alsengemmen are two-layer glass gems, imitating the nicolo and deriving their name from a specimen found in the Danish island of Als. This article presents six new specimens from Brescia coming in addition to those of the existing catalogues, which number 193 items, together with a chart making an inventory of and describing a series of 135 gems. It provides an opportunity for fresh reflection on the distribution and chronology of these peculiar gems, some of which were reused in liturgical objects in the Middle Ages, in such areas as the Netherlands, Rhenany-Westphalia and Lower Saxony.